Primary peritoneal clear cell carcinoma - A diagnostic dilemma - Agarwal, Deepti; Jaiswal, Milan (Indian Journal of Case Reports, 2020)
Peritoneum is a site for both primary and secondary tumors. Clear cell carcinoma of the peritoneum is an extremely rare primary tumor. The diagnosis of primary peritoneal tumors is based on the gynecology oncology group criteria, originally described for primary adenocarcinoma of the peritoneum. A 55-year-old female presented with non-specific pain in the lower abdomen of 1-month duration. Contrast-enhanced computed tomography findings of the abdomen were suggestive of suspected neoplastic mass most likely arising from the left ovary. Pre-operative serum cancer antigen-125 levels were 252 U/ml. Upon exploratory laparotomy, a hard nodular mass appearing to arise from anterior abdominal wall (15 × 12 cm) was found in the left iliac fossa. Histopathological diagnosis of primary peritoneal clear cell carcinoma was made and immunohistochemistry was performed for confirmation.